Integration of Multicultural Values in Islamic Religious Education Learning - Asnani M Saula; Andi Anirah; Fatimah Saguni; Idris; Aniati (Edudeena : Journal of Islamic Religious Education, 2026)
The increasing diversity of ethnicity, religion, culture, and social backgrounds in school environments requires Islamic Education (PAI) to move beyond a mere focus on mastering religious knowledge and instead emphasize the strengthening of tolerant and inclusive attitudes that respect differences. While multicultural education has been widely studied, the implementation of integrating multicultural values ​​into Islamic Education instruction in vocational high schools still requires deeper empirical analysis. This study aims to analyze how multicultural values ​​are integrated into Islamic Education instruction at SMKN 1 Sigi and to identify the factors that facilitate or hinder this implementation. A qualitative approach with a case study design was employed. Data were gathered through observations, in-depth interviews with Islamic Education teachers, school administrators, and students, as well as an analysis of instructional documents. The data were analyzed using thematic analysis, involving data reduction, data display, and conclusion drawing. The findings indicate that the integration of multicultural values ​​is achieved through the development of an inclusive curriculum, extracurricular activities, and social interactions that foster respect for diversity. This implementation contributes to cultivating tolerance, mutual respect, and the students' ability to live harmoniously within a pluralistic society. However, the implementation still faces challenges, specifically limited teacher competence regarding multicultural education and a lack of optimal student understanding of diversity values. This study underscores that integrating multicultural values ​​into Islamic Education requires strengthening teacher competence, developing contextual teaching materials, and establishing school policies that foster an inclusive learning culture